The Influence of Trust, Income, and product Knowledge on Female College Students in Malang City in Purchasing Wardah Cosmetic Products - Anisa Nurmawati; Sri Muljaningsih (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this study is to examine the effect of trust, income, and product knowledge on female college students in their purchase of Wardah cosmetics in Malang City. This research is based on the competitive landscape of the cosmetic market in Indonesia, where access to foreign cosmetic products whose halal status is not guaranteed is very easy. Therefore, the researcher aims to investigate the effect of several selected variables on the purchase of Wardah, a local cosmetic brand that has been certified as halal. This study used a quantitative research design, with the independent variables being trust (X1), income (X2), and product knowledge (X3), and the dependent variable being product purchase (Y). The analytical method used is multiple regression analysis by processing data from 40 respondents in Malang City. The results of the study showed that the income variable (X2), based on its indicators, had a positive and significant effect on the product purchase variable (Y), while the trust variable (X1) and product knowledge variable (X3) had a positive but insignificant effect on product purchase (Y). The researcher concludes that the purchase of Wardah cosmetic products by female college students in Malang City will increase if trust, income, and product knowledge also increase.